Warfare and society: archeology and social anthropological perspectives - Otto, Ton; Thrane, Henrik; Vandkilde, Helle (2006)
Abstract: While it may be overkill to say that studying war is hell, it is certainly problematic. To participants, war is chaos, death and boredom and hence incommunicable. To scholars who do not know the smell of gunpowder, war is mediated by silent artefacts and layered discourse. They must muster compassion without letting it distort analysis. And despite entrenched traditions to the contrary, war cannot be comprehended in isolation from society. To better understand the complex relationships between war and society, the two dozen contributors to this volume employ a broad variety of archaeological and anthropological tools, drawing where appropriate on history, political science and philosophy. The chapters are grouped under several heads, each prefaced by a helpful introduction. Topics include the theoretical conceptions of war in various disciplines; war in pre-state societies, and its relation to state formation; ritual war and mass graves; ancient weaponry and material culture; and w